Dynamic Adaptive Policy Pathways Approach to Manage Climate and Land Use Change‐Induced Urban Flood Damages - Arash Majidi; Seyed Abbas Hosseini (Journal of Flood Risk Management)
ABSTRACT Flood management in urban areas requires innovative and adaptive strategies to address the growing challenges posed by climate change, land use transformations, and socio‐economic developments. This study provides a comprehensive analysis of the complex interactions within an urban area using integrated modeling approaches, offering critical insights into potential future challenges. These approaches incorporate climate, land use, hydrological, hydraulic, and damage models, complemented by an adaptation pathways map and recommendations for the most effective strategies, conducted in a flood‐prone urban area. The analysis projects an increase by 2080 of 3.39°C in temperature, 46% in precipitation, and 29% in flood‐related damages. The study underscores the substantial impact of land use changes on flood damages, highlighting the need for integrating land use planning into flood mitigation strategies. A rigorous evaluation identified a combination of measures—including concrete dyke construction, dredging, afforestation, and forest conservation—as effective actions for mitigating flood risks in the region near the Caspian Sea. Forest conservation and afforestation reduce peak flood discharge by 12.2% and 23.1%, respectively, for a 100‐year return period. Economic evaluations were performed for all adaptation pathways to assess their feasibility and cost‐effectiveness. Using the Analytic Hierarchy Process (AHP), the study determined that the optimal strategy is the simultaneous implementation of concrete dyke construction, dredging, and forest conservation. Additionally, six adaptation pathways were defined through the Dynamic Adaptive Policy Pathways (DAPP) method to provide a structured roadmap for implementing and adjusting flood management measures over time. These pathways aim to reduce potential future flood damage to negligible levels. Overall, this research highlights the importance of adopting integrated and adaptive strategies to address the multi‐faceted challenges posed by environmental changes, ensuring effective flood management amidst growing deep uncertainties.